Changing the mindsets? Education and the intergenerational spread of tolerance for physical violence against women in Zimbabwe - Makate, Marshall; Nyamuranga, Chamunorwa (Elsevier, 2023)
We investigate the relationship between childhood exposure to interparental violence and adult tolerance for violent beliefs against women. For individuals who have witnessed parental violence in childhood, our analysis suggests a 14.3–15.2 percentage point (pp) increase in tolerance, highlighting the transmission of violent beliefs across generations. Leveraging Zimbabwe’s 1980 education reform as a natural experiment through a regression discontinuity design, we explore the potential of increased education to disrupt this intergenerational transmission. The reform led to an approximately two-year increase in female education, with a more pronounced impact in rural areas. This educational boost is associated with an estimated 4.1–7.9 pp reduction in tolerance for violence, especially among those who witnessed parental violence in childhood. We identify four primary mechanisms contributing to this reduction in tolerance: enhanced access to information, increased help-seeking behaviours, improved labour market outcomes, and higher educational levels among partners. Our findings underscore the effectiveness of educational policies in reducing tolerance for violence against women within low-income contexts such as Zimbabwe, thereby disrupting its intergenerational transmission. Moreover, these results emphasise the potential of education-based interventions in addressing the broader issue of violence against women in low-income countries.